SME surface mining handbook - Darling, Peter, 1956- (Society for Mining, Metallurgy & Exploration, 2023)
"This landmark publication distills the body of knowledge that characterizes surface mining as a disciplinary field. It will inspire and inform current and future generations of mining professionals. It describes the major methodologies involved in the surface extraction or ores, highlights the direction of change, and examines and communicates the major developments within the sector"--